Triphenylsulfophosphonium chlorometallates as efficient heterogeneous catalysts for the three-component synthesis of 2, 3-dihydro-1, 2, 3-trisubstituted-1H-naphth[1, 2-e][1, 3]oxazines. (17th February 2017) - Dutta, Arup Kumar; Gogoi, Pinky; Borah, Ruli
Graphical abstract: Four new P-sulfonic acid functionalized phosphonium chlorometallates were prepared as stable acidic solids and studied as reusable heterogeneous catalysts for the three-component synthesis of anti -2, 3-dihydro-1, 2, 3-trisubstituted-1 H- naphth[1, 2-e][1, 3]oxazines in solution and under solvent-free conditions. Abstract: Four new SO3 H functionalized triphenylsulfophosphonium chlorometallate ionic salts [TPSP] n [X], where n = 1 or 2 and X = FeCl4 −, Zn2 Cl6 2−, NiCl4 2−, MnCl4 2−, were developed as stable solid acidic materials and characterized via NMR, FT-IR, Raman, TGA, powder XRD, UV–Vis, SEM-EDX, ICP and CHN elemental analyses. All these solids were evaluated as heterogeneous catalysts for the multicomponent synthesis of anti -2, 3-dihydro-1, 2, 3-trisubstituted-1 H- naphth[1, 2-e][1, 3]oxazines from a mixture of 2-naphthol, aryl aldehyde and a nucleophilic primary amine by stirring in 50% aqueous ethanol at room temperature and under neat conditions at 80 °C.